2021
DOI: 10.1101/2021.11.17.468999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reversible bacteriophage resistance by shedding the bacterial cell wall

Abstract: Phages are highly abundant in the environment and a major threat for bacteria. Therefore, bacteria have evolved sophisticated defense systems to withstand phage attacks. Here, we describe a previously unknown mechanism by which mono- and diderm bacteria survive infection with diverse lytic phages. Phage exposure leads to a rapid and near complete conversion of walled cells to a cell wall-deficient state, which remain viable in osmoprotective conditions and can revert to the walled state. While shedding the cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…All data are available in the main text and electronic supplementary material [43]. Phage genome sequencing data are available on NCBI (GenBank accession no.…”
Section: Data Accessibilitymentioning
confidence: 99%
“…All data are available in the main text and electronic supplementary material [43]. Phage genome sequencing data are available on NCBI (GenBank accession no.…”
Section: Data Accessibilitymentioning
confidence: 99%
“…There are many conditions that can generate CWD variants. These include exposure to cell wall degrading enzymes [44,[52][53][54]; heat stress [55]; cryogenic stress [56]; osmotic stress [57,58]; nutrient limitation [55,56,59]; genotoxic stress [14]; antibodies and complement proteins [60,61]; bacteriophages [61,62]; compounds that inhibit cell wall biosynthesis [54,63]; and mutation of genes involved in cell wall biosynthesis [24,46,64,65]. In this section, we will address whether the method by which a CWD state is achieved results in differences in the viability, robustness and physiology of the resulting CWD variant.…”
Section: Generation Of Cwd Bacteriamentioning
confidence: 99%
“…With the challenges of antibiotic resistance, phage therapy has been seen as a promising addition to the treatment options. However, from the very early days of research into CWD bacteria, bacteriophage treatment has been reported to induce CWD forms [61,62]. A recent study found that E. coli strains that were exposed to meropenem to induce the formation of CWD cells were able to resist the action of bacteriophages [117].…”
Section: Implications Of Transient Cwd Bacteria In Antibiotic Tolerancementioning
confidence: 99%
“…However, the interactions between bacteriophages and Streptomyces and the underlying mechanisms remain largely unexplored. Besides the phage growth limitation system 8,9 and recently discovered cell wall-de ciency 10 , many more defense mechanisms against phage attack might be present in Streptomyces. In addition, relatively few Streptomyces phages have been properly sequenced and characterized in comparison to other genera.…”
Section: Introductionmentioning
confidence: 99%